Enhancing Central Nervous System Repair-The Challenges - Xu, Xiaohua (2011)
Repair of the central nervous system (CNS) constitutes the integral part in treating neurologic diseases and plays a crucial role in restoring CNS architecture and function. Distinct strategies have been developed to reconstruct the damaged neural tissue with most of them tested preclinically in animal models. In this review, we discuss cell replacement based repair strategy and rewiring of the CNS. We review the major challenges of CNS repair by focusing on neurodegeneration and the pathological obstacles which impede neural cell growth after CNS injury. Finally, we discuss recent progress in developing human monoclonal IgMs that regulate CNS homeostasis and promote neural regeneration.